2019
DOI: 10.1038/s41598-019-51919-x
|View full text |Cite
|
Sign up to set email alerts
|

Association between newborn screening analytes and hypoxic ischemic encephalopathy

Abstract: Hypoxic ischemic encephalopathy (HIE) is a major cause of neonatal mortality and morbidity. Our study sought to examine whether patterns of newborn screening analytes differed between infants with and without neonatal HIE in order to identify opportunities for potential use of these analytes for diagnosis in routine clinical practice. We linked a population-based newborn screening registry with health databases to identify cases of HIE among term infants (≥37 weeks’ gestation) in Ontario from 2010–2015. Correl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…HIE is a brain dysfunction related to oxygenation and blood flow insufficiency [ 17 ]. Our research has confirmed that CNP has a good application effect in the care of NHIE, which can significantly promote the PMD, intelligence development, ND, and physique growth of HIE children with a favorable safety profile.…”
Section: Discussionmentioning
confidence: 99%
“…HIE is a brain dysfunction related to oxygenation and blood flow insufficiency [ 17 ]. Our research has confirmed that CNP has a good application effect in the care of NHIE, which can significantly promote the PMD, intelligence development, ND, and physique growth of HIE children with a favorable safety profile.…”
Section: Discussionmentioning
confidence: 99%
“…42 Moreover, clinical studies have shown that the severity of brain injuries in male newborns is higher than that in female newborns, and the recovery ability of males is lower than that of females. 43,44 Kuboyama et al 45 found that in a primary mixed mouse glial cell culture, PTN treatment enhanced the differentiation of OL lineage cells into MBP-positive mature OLs. Goebbels et al 18 showed that in primary OL cultures, adding recombinant human protein PTN could effectively stimulate myelination.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in our study, we only selected male rats because other studies indicated that male neonatal rats had more severe brain damage than female rats under the same conditions 42 . Moreover, clinical studies have shown that the severity of brain injuries in male newborns is higher than that in female newborns, and the recovery ability of males is lower than that of females 43,44 …”
Section: Discussionmentioning
confidence: 99%
“…NSO is equipped with sufficient personnel and laboratory resources to accommodate the inclusion of international clinical and research samples into the organization's standard workflow. The organization is currently providing newborn screening services to remote communities in other Canadian provinces/territories, and has piloted international screening services 14 .…”
Section: Patient Consentmentioning
confidence: 99%